2001
DOI: 10.1111/j.1542-474x.2001.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Ventricular Repolarization with Flecainide in Long QT Syndrome Patients with SCN5A:ΔKPQ Mutation

Abstract: Background:The Long QT Syndrome (LQTS) i s a genetic channelopathy with life-threatening implications. The LQT3 form of this disease is caused by mutations of the SCN5A sodium-channel gene. A specific mutation, SCN5A:AKPQ, is associated with repetitive reopenings of the sodium channel and prolonged inward current. This dominant inward current is manifest on the electrocardiogram as QT prolongation. Flecainide is a potent blocker of the open sodium channel. Methods and Results: The effect of flecainide on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 20 publications
1
77
0
Order By: Relevance
“…Similar shortening of the QTc interval in LQT3 patients with the ∆KPQ deletion has been reported with lidocaine and tocainide (22). Preliminary clinical experience with flecainide revealed normalization of the QTc interval with low doses of this drug in patients with the ∆KPQ deletion (23). In 2000, Benhorin et al reported the effectiveness of open-label oral flecainide in shortening the QTc interval in 8 asymptomatic subjects with the D1790G mutation (24).…”
Section: Gene-specific Triggers Of Cardiac Arrhythmiasmentioning
confidence: 99%
“…Similar shortening of the QTc interval in LQT3 patients with the ∆KPQ deletion has been reported with lidocaine and tocainide (22). Preliminary clinical experience with flecainide revealed normalization of the QTc interval with low doses of this drug in patients with the ∆KPQ deletion (23). In 2000, Benhorin et al reported the effectiveness of open-label oral flecainide in shortening the QTc interval in 8 asymptomatic subjects with the D1790G mutation (24).…”
Section: Gene-specific Triggers Of Cardiac Arrhythmiasmentioning
confidence: 99%
“…45 The use of sodium channel blockers such as flecainide and mexiletine is also beneficial in LQT3. 46,47 Rarely, more aggressive interventions such as sympathetic denervation surgery or implantable defibrillators are needed in high-risk cases, such as the cardiac arrest survivor, patients with persistent symptoms despite ␤-blocker therapy, patients with QTc intervals persistently Ͼ550 ms, or symptomatic patients with Ͼ1 genotype (compound heterozygotes). 48,49 Although sympathetic denervation surgery has traditionally been used as an adjunct to defibrillator therapy, its safety and therapeutic success in the era of minimally invasive thoracoscopic surgery have raised its profile, and it should now be considered as a therapeutic option before ICD implantation in drug-refractory cases.…”
Section: Prognosis and Therapymentioning
confidence: 99%
“…12 By 1991, we expanded the prospective study of the clinical course of this disorder to 1016 affected individuals in 328 LQTS families. 13 Important findings from the Registry during the past decade have included the following: age-and sex-related differences in the clinical manifestations of LQTS 14 ; influence of pregnancy on the risk for cardiac events in LQTS 15 ; ECG T-wave patterns in genetically distinct forms of LQTS 16 ; clinical course of LQTS by genotype 17 ; the spectrum of mutations in LQTS genes 18 ; increased risk associated with mutations in the pore region of the hERG gene 19 ; role played by physical exercise, emotions, arousal, and rest/sleep as triggers and facilitators for syncope and sudden cardiac death in LQT1, LQT2, and LQT3 20 -22 ; effectiveness of ␤-blocker therapy, particularly in patients with LQT1 and LQT2 genotypes 23 ; potential gene-specific usefulness of sodium channel blockers (mexiletine and flecainide) in the treatment of patients with the LQT3 mutations 24,25 ; life-saving benefit from the implanted defibrillator in highrisk LQTS patients 26 ; and left cardiac sympathetic denervation in the management of high-risk LQTS patients. 27 We initially thought that the clinical benefit of left-sided sympathectomy might have come from either a correction of a hypothesized left-sided dominance of sympathetic innervation or, in the case of a yet undefined "myocardial abnormality" (subsequently found to be represented by the mutations in cardiac ion channel genes), from removal of an arrhythmogenic trigger.…”
Section: Findings From the Registrymentioning
confidence: 99%